2011
DOI: 10.1007/s00704-011-0499-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for a quasi 60-year North Atlantic Oscillation since 1700 and its meaning for global climate change

Abstract: The North Atlantic Oscillation (NAO) obtained using instrumental and documentary proxy predictors from Eurasia is found to be characterized by a ~60-year dominant oscillation since 1650. This pattern emerges clearly once the NAO record is time integrated to stress its comparison with the temperature record. The integrated NAO (INAO) is found to well correlate with the Length of the Day (LOD) (since 1650) and the global surface sea temperature (SST) record (since 1850). These findings suggest that INAO is an ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 33 publications
2
58
1
1
Order By: Relevance
“…Indeed, despite the IPCC (2007) claims the sun has an almost negligible effect on climate, numerous authors found significant correlations between specific solar models and temperature records suggesting a strong climate sensitivity to solar variations (e.g. : Bond et al 2001;Hoyt and Schatten 1993;Loehle and Scafetta 2011;Mazzarella and Scafetta 2012;Ogurtsov et al 2002;Scafetta 2009Scafetta , 2010Scafetta , 2012bScafetta , 2013bSchulz and Paul 2002;Soon 2005;Soon and Legates 2013;Steinhilber et al 2012;Svensmark 2007;Thejll and Lassen 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, despite the IPCC (2007) claims the sun has an almost negligible effect on climate, numerous authors found significant correlations between specific solar models and temperature records suggesting a strong climate sensitivity to solar variations (e.g. : Bond et al 2001;Hoyt and Schatten 1993;Loehle and Scafetta 2011;Mazzarella and Scafetta 2012;Ogurtsov et al 2002;Scafetta 2009Scafetta , 2010Scafetta , 2012bScafetta , 2013bSchulz and Paul 2002;Soon 2005;Soon and Legates 2013;Steinhilber et al 2012;Svensmark 2007;Thejll and Lassen 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Ice core analysis suggests a shorter AMO quasi-periodicity (about 20 years) during the Little Ice Age and a longer periodicity in the Medieval Warm Period (Chylek et al 2012). Atmosphere-Ocean coupled climate models (Metha and Delworth 1995;Griffies and Bryan 1997;Delworth and Knutson 2000;Dong and Sutton 2001;Wei and Lohmann 2012;Mahajan et al 2011;Henriksson et al 2012;Yang et al 2013;Escudier et al 2013;Zanchettin et al 2013) as well as simplified conceptual ocean models (Frankcombe and Djikstra 2011), or statistical harmonic models (Humlum et al 2011;Mazzarella and Scafetta 2012;Scafetta 2012) suggest a future persistent AMO like multi-decadal oscillation. Based on this evidence of the past behavior we expect the AMO to retain its cyclic behavior during the twenty-first century with a cycle length of 60-70 years.…”
Section: Discussionmentioning
confidence: 97%
“…Cycles with quasi 50-70-year periods are found in several climatic records (Wyatt et al 2011), particularly in the global surface temperature since 1850 (Scafetta 2010(Scafetta , 2012a and are clearly present in the North Atlantic Oscillation indexes since 1700 (Mazzarella and Scafetta 2012).…”
Section: Short-term Modern Climate Forcingmentioning
confidence: 93%